Integration of Social Entrepreneurship and Corporate Social Responsibility Through the Triple Helix Framework in DTSEN-Based Poverty Alleviation Policies: Systematic Literature Review and Research Agenda - Nayla Khairunnisa Mutaqien; Harry Z. Soeratin (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study aims to identify research directions and theoretical contributions regarding the integration of Social Entrepreneurship (SocEn) and Corporate Social Responsibility (CSR) through the Triple Helix framework in the context of poverty alleviation policies based on Integrated Social Welfare Data (DTSEN) as stipulated in Presidential Instruction No. 4 of 2025. Through a systematic analysis of 15 journals (5 Scopus, 2 Sinta 2, 2 Sinta 3, and 6 Sinta 5), ​​this study identifies three main research gap dimensions. Theoretically, there is no integrative framework connecting SocEn, CSR, and the Triple Helix in the context of DTSEN. Empirically, there are limited studies measuring standardized social impacts and multi-stakeholder collaboration. Contextually, research in developing countries, especially Indonesia, is still limited in exploring the role of digitalization and local wisdom. Research recommendations include the development of a data-driven collaborative model to increase the effectiveness of poverty alleviation programs through academia-business-government synergy supported by digital transformation.